Evaluation of the Efficacy of Treatment of Newborns with Transient Myocardial Ischemia - Yulia N. Dovnar; Alla A. Tarasova; Ivan F. Ostreykov; Vladimir N. Podkopaev (Общая реаниматология)
The purpose of the study: a comprehensive assessment of the effectiveness of the treatment of newborns with transient myocardial ischemia in the intensive care unit.Materials and methods. 102 newborns with transient myocardial ischemia, with a history of ante- and/or intranatal hypoxia, at the age of 1 to 7 days, with a gestational age from 29 to 42 weeks, underwent a clinical and instrumental examination of the heart before and during the treatment. The Group 1 consisted of 30 infants with 1 degree circulatory failure (CF); the Group 2 was comprised of 39 infants with 2A degree of CF, and the Group 3 included 33 infants with the 2B degree of CF. All children received cardiotropic drugs; infants from Groups 2 and 3 received cardiotonic drugs.Results. The study demonstrated an increase in biochemical parameters of blood (myocardial CPK, lactate dehydrogenase, aspartate aminotransferase, de Ritis ratio), manifestations of subendocardial ischemia in the electrocardiogram (depression of ST segment in one or more leads in combination with a T-wave defect), changes in systolic cardiac function during echocardiography (stroke volume, ejection and shortening factions, left ventricular TEI index, cardiac output, and cardiac index) that correlated with the severity of myocardial ischemia and circulatory failure and their reverse development during the treatment. Various correlative links between parameters of left ventricular systolic function and blood biochemistry before and during the treatment reflecting the myocardial dysfunction with a gradual reverse development have been found.Conclusion. Infants with transient myocardial ischemia suffered from disorders of the clinical and functional state of the heart depending on the degree of ischemia and circulatory failure. Most infants exebited gradual reverse development during a complex intensive therapy.